ANXIOLYTIC ACTIVITY EVALUATION OF FOUR MEDICINAL PLANTS FROM CAMEROON - Bum, Ngo; Soudi, S; Ayissi, E R; Dong, C; Lakoulo, N H; Maidawa, F; Seke, P F E; Nanga, L D; Taiwe, G S; Dimo, T; Njikam, N; Rakotonirina, A; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Afrormosia laxiflora (A. laxiflora), Chenopodium ambrosioides (C. ambrosioides), Microglossa pyrifolia (M. pyrifolia) and Mimosa pudica (M. pudica) are plants used in traditional medicine in Cameroon to treat insomnia, epilepsy, anxiety, and agitation. They were evaluated for their anxiolytic like activity in mice. Animal models (elevated plus maze and stress-induced hyperthermia tests) were used. The four plants showed anxiolytic activity. In stress-induced hyperthermia test, A. laxiflora, C. ambrosioides, M. pyrifolia and M. pudica significantly antagonised the increase of temperature. ΔT° decreased from 0.75°C in the control group to 0.36°C at the dose of 110 mg/kg for A. laxiflora; from 1°C in the control group to -1.1°C at the dose of 120 mg/kg for C. ambrosioides; from 1.7°C in the control group to 0.2°C at the dose of 128 mg/kg for M. pyrifolia and from 1.3°C in the control group to 0.5°C at the dose of 180 mg/kg for M. pudica. In the elevated plus maze test, the four plants increased the number of entries into, percentage of entries into, and percentage of time in open arms. A. laxiflora, C. ambrosioides and M. pudica also reduced the percentage of entries and time in closed arms. In addition, C. ambrosioides, M. pyrifolia and M. pudica showed antipyretic activity by reducing the body temperature. The results suggested that C. ambrosioides, M. pyrifolia and M. pudica posses anxiolytic-like and antipyretic activities while A. laxiflora possesses only anxiolytic-like properties. These plants could be helpful in the treatment of anxiety and fever in traditional medicine in Cameroon.